PHILOSOPHICAL ASPECT FOR INSTITUTIONALIZES OF LIBRARIES - Азнакаєва, Е. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The philosophical concepts for institutionalizes of libraries of an information society are considered in article.